Efficacy of terpenoids in attenuating pulmonary edema in acute lung injury: A meta-analysis of animal studies - Shuai Wang; Sean X. Luo; Jing Jie; Dan Li; Han Liu; Lei Song (Frontiers in Pharmacology, 2022)
Background: The clinical efficiency of terpenoids in treating human acute lung injury (ALI) is yet to be determined. The lipopolysaccharide-induced rat model of ALI is a well-established and widely used experimental model for studying terpenoids’ effects on ALI. Using a systematic review and meta-analysis, the therapeutic efficiency of terpenoid administration on the lung wet-to-dry weight ratio in rats was investigated.Methods: Using the Cochrane Library, Embase, and PubMed databases, a comprehensive literature search for studies evaluating the therapeutic efficacy of terpenoids on ALI in rats was conducted. The lung wet-to-dry weight ratio was extracted as the main outcome. The quality of the included studies was assessed using the Systematic Review Center for Laboratory Animal Experimentation’s risk of bias tool.Results: In total, 16 studies were included in this meta-analysis. In general, terpenoids significantly lowered the lung wet-to-dry weight ratio when compared with the control vehicle (p = 0.0002; standardized mean difference (SMD): −0.16; 95% confidence interval (CI): −0.24, −0.08). Subgroup analysis revealed that low dose (≤10 μmol/kg) (p < 0.0001; SMD: −0.68; 95% CI: −1.02, −0.34), intraperitoneal injection (p = 0.0002; SMD: −0.43; 95% CI: −0.66, −0.20), diterpenoid (p = 0.004; SMD: −0.13; 95% CI: −0.23, −0.04), and triterpenoid (p = 0.04; SMD: −0.28; 95% CI: −0.54, −0.01) significantly lowered the lung wet-to-dry weight ratio when compared with the control vehicle.Conclusion: A low dose of diterpenoid and triterpenoid administered intraperitoneally is effective in alleviating ALI. This systematic review and meta-analysis provides a valuable mirror for clinical research aiming at the advancement of terpenoids for preventive and therapeutic use.Systematic Review Registration: CRD42022326779